(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and subclinical characteristics of stillbith over 3 months at the Obstetrics Department of A Thai Nguyen Hospital from January 2019 to December 2023. Research subjects and methods: Descriptive cross-sectional study method, retrospective descriptive research method on 102 patients with medical records diagnosed with stillbirth from 13 weeks or more to the hospital and treated at the Obstetrics Department - A Thai Nguyen Hospital from January 1, 2019 to the end of December 2023. Results: The average age of pregnant women with stillbirth is 29.09 ± 5.716 years old. The rate of vaginal bleeding was 25.5%; abdominal pain 14.7%; loss of fetal movement 18.6%, pregnancy examination 34.3%. Stillbirth age ranges from 13 to 21 weeks, accounting for 56.9%. Signs of no fetal heart activity on ultrasound accounted for 100%, signs of skull overlap were 9,8%, and the rate of polyhydramnios and oligohydramnios was 13.7%. The rate of stillbirth with fibrinogenesis ≥ 2 is 100%, Prothrombin ≥ 70% is 100%. Stillbirth with hemoglobin ≥ 110g/l accounts for 95.1%, less than 110g/l accounts for 4.9%. Conclusion: Mainly pregnant women of reproductive age. Stillbirth age over 3 months is mainly in the 13 - 21 weeks group. 100% of stillbirth have no fetal heart activity on ultrasound. No patient had a coagulation disorder.